An Africander collection - Hook, Derek (PINS-Psychology in Society, 2025)
Crais, Clifton & McClendon, Thomas (2014). The South Africa reader: History, culture, politics. Durham, NC & London: Duke University Press. ISBN 978-0-8223-5529-8. Pages 604. Of the many challenges that the editors of Duke University’s new South Africa reader faced was the obvious one: what, amongst so wide a range of contemporary and historical material, should be included? The problem is exacerbated by the book’s stated remit, as outlined in the book’s subtitle, “History, culture, politics”. This announces an expansive agenda and confers upon the editors the responsibility of including key selections from each of these three areas. Of course, every literary scholar or intellectual interested in South African history and culture will have quibbles regards what has not been included and what has. Some observations in this respect open up onto broader issues related to the efficacy of critical historical juxtaposition and the need to recover rather than merely reproduce history.